Fossil woods from the Eocene-Oligocene (Río Turbio Formation) of southwestern Patagonia (Santa Cruz province, Argentina) - Pujana, Roberto Roman; Ruiz, Daniela Paula (IAWA Journal)
Over 80 samples of fossil woods were collected from numerous outcrops of the Río Turbio Formation, southwestern Patagonia. Preservation of the woods is variable and only about half of these samples could be identified to genus level. The assemblage consists of six types of conifers and four types of dicotyledons, one of them a new species of Caldcluvioxylon (Cunoniaceae). We provide an emended diagnosis of Caldcluvioxylon. A previously described fossil wood from this stratigraphic unit, thought to have affinity with Proteaceae, was reexamined and is described herein as Scalarixylon romeroi sp. nov. Other families recognized in the Río Turbio Formation wood assemblage are Araucariaceae, Podocarpaceae, and Nothofagaceae. Differences in the taxonomic composition of the upper and lower members of the Río Turbio Formation are consistent with the age difference between them according to recent isotopic dating. The diversity of fossil wood is also consistent with the fossil leaves and pollen from each stratigraphic level and most of the taxa are shared with coeval Antarctic fossil wood floras. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Ruiz, Daniela Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina